The venous contribution to cardiovascular performance: from systemic veins to left ventricular function - a review - Bombardini, Tonino (Scripta Medica, 2021)
The venous system contains ≈ 70 % of the total blood volume and is responsible in heart failure for key symptoms of congestion. It is active: it can increase or relax its tone with physiologic or pharmacologic stimuli. It is heterogeneous, behaves as a two-compartment model, compliant (splanchnic veins) and noncompliant (nonsplanchnic veins). It is dynamic in health and disease: in heart failure the vascular capacitance (storage space) is decreased and can result in volume redistribution from the abdominal compartment to the thoracic compartment (heart and lungs), which increases pulmonary pressures and precipitates pulmonary congestion. A noninvasive assessment of venous function, at rest and dynamically during stress, is warranted. The systemic haemodynamic congestion is assessed with inferior vena cava diameter and collapsibility. The pulmonary congestion is assessed with B-lines and pleural effusion. The contribution of left ventricular filling is assessed with end-diastolic volume, integrated with left ventricular function.
Keywords: Venous return; Ventricular function; Central venous pressure; Mean systemic pressure